Events, lines and interruptions: the production of university space - de Villiers, Isolde (Acta Academica: Critical views on society, culture and politics, 2019)
During 2015 and 2016 there were wide-spread student protests across campuses in South Africa. This contribution focuses on the protests at the University of Pretoria and in particular the way in which the spatiality of the campus and the city of Tshwane influenced the nature of the protests. In terms of the spatiality of the campus, I consider in particular the neo-brutalist architecture of the campus, the fact that it is fencedoff entirely and also its restrictive events policy. Within the city of Tshwane, the focus falls on a long history of marching to the Union Buildings as well as the Regulation of Gatherings Act, and how that related to the student protests. This contribution contrasts Michel Foucault’s notion of heterotopia with Henri Lefebvre’s concrete utopia, to call for universities to be concrete utopias. The student protests are framed as lines and as interruptions with reference to the work of Antonia Layard. Even though the student protests at the University of Pretoria can be distinguished from those on other campuses, it is connected and contextualised within the broader student movement through Doreen Massey’s concept of geographies of responsibility.